Lactylation and antitumor immunity - Yang, Biao; Li, Lingyu; Shi, Dongmei; Zhong, Tao; Xiong, Huabao (Frontiers in Immunology, 2025)
Lactylation, a recently discovered post-translational modification (PTM), plays a critical role in cancer biology. Warburg effect induces lactate accumulation, which serves as a metabolic end-product and intercellular signaling mediator within the tumor microenvironment (TME). Beyond fueling tumor growth, elevated lactate levels drive histone and non-histone lactylation, which modulates gene expression and protein function. This epigenetic reprogramming induces immunosuppressive phenotypes in immune cells that are resident in the tumor microenvironment, including impaired effector function, enhanced immunosuppressive cytokine secretion, and altered tumor antigen presentation, collectively facilitating immune escape. This review provides a synthesis of the current understanding of lactate and lactylation in tumor immunosuppression, detailing molecular mechanisms underlying immune cell inhibition (tumor-associated macrophages, T cells, T-reg cells, NK cells and NKT cells, as well as neutrophils) and evaluating emerging therapeutic strategies (e.g., inhibitors of MCTs/LDHA, site-specific antibodies, genetic code expansion technology). We aimed to accelerate the clinical translation of lactylation-targeted anticancer therapies by highlighting recent advances.